Analisis Kurang Optimalnya Pembuangan Air Ballast Pada Kapal MV DK 02 - Yusuf Adi Pratama; Arya Widiatmaja; Fatimah (Politeknik Ilmu Pelayaran Semarang, 2024)
The ballast system is a critical component that ensures a ship's balance on the water.However, if the ballast system does not operate optimally, it can hamper the loading and unloadingprocess and disrupt the stability of the ship. This study aims to identify the factors that lead to sub-optimal ballast water discharge, its impact, and efforts to overcome it. Using a qualitative approach,data were obtained through observation, interviews and documentation, and analysed usingfishbone diagrams and interactive analysis models. The validity of the data was confirmed usingtriangulation method by the first mate responsible for the ballast system. The results showed thatdamage to the ballast pumps, valves and pipes, as well as leaks in the hull were the main causes ofsub-optimal ballast water discharge on the MV. DK 02. This has an impact on hampering theloading and unloading process and disrupting the stability of the ship. Therefore, regular checkson ballast components and adequate availability of spare parts are required to ensure the ballastsystem functions optimally.